IMPACT OF CLIMATE CHANGE ON FINANCIAL SUSTAINABILITY IN AGRICULTURAL INDUSTRIES - Adiatma, T; Irianto, O; Hyronimus, D; Kuntag, J R (Universitas Tadulako, 2024)
Climate change nowadays became the most problematic matter including in agricultural industries. Agriculture area productivity affected national food security and a county’s economic development. As an agricultural county, Indonesia must be ready to adapt and prepare for the worst impact of climate change. This paper aims to explore the impact of climate change on financial sustainability in agricultural industries. This research uses a systematic literature review method related to financial sustainability, climate change impact, and agriculture industries. The result shows that financial sustainability in agricultural industries must be impacted by climate change. The impact of climate change on agriculture industries is associated with reducing profitability, destroying capital, portfolio reallocation, and financial instability. Climate change caused environmental uncertainty that affects agricultural productivity. To reduce the impact of climate change on financial sustainability in agricultural industries, there must be a design of mitigation must be prepared and realized so agricultural industries are more prepared and ready to face climate change impact.